AB0824 WHICH PARAMETERS ARE RELEVANT IN THE IDENTIFYING AXIAL INVOLVEMENT IN PSORIATIC ARTHRITIS? – RESULTS OF A SURVEY AMONG ASAS AND GRAPPA MEMBERS. (2nd June 2020) - Poddubnyy, D.; Mease, P. J.; Van den Bosch, F.; Braun, J.; Gottlieb, A.; Coates, L. C.; Chandran, V.; Helliwell, P.; Jadon, D.; Sieper, J.; Van der Heijde, D.; Gladman, D. D.
Abstract : Background: Inflammatory involvement of the axial skeleton (sacroiliac joints and / or spine) is one of the relatively frequent musculoskeletal manifestations associated with psoriasis / psoriatic arthritis (PsA). There is an urgent need for an evidence-based definition for axial involvement in PsA that would identify a subgroup of patients within the heterogeneous PsA population to conduct observational, interventional and translational studies. ASAS and GRAPPA embarked on a collaborative initiative to develop a definition of axial involvement in PsA. Objectives: To perform a survey to identify variables relevant in the identification of the presence of axial involvement in PsA among members of ASAS and GRAPPA. Methods: The online survey utilized the PAPRIKA methodology ( P otentially A ll P airwise R an K ings of all possible A lternatives ) that determines decision-makers' part-worth utilities representing the relative importance of the attributes. Participants were exposed to number of clinical scenarios and were prompted to decide which of the scenarios is more compatible with axial involvement in PsA unless they are equal (Figure ). The constant stem of each scenario was "a patient diagnosed with psoriatic arthritis fulfilling the CASPAR criteria"; the variable part included 13 common spondyloarthritis variables (Table ). Variables were ranked according to their relative importance. Results: The survey was completed by 186 ASAS/GRAPPA members (63 ASAS only, 80 GRAPPA only, and 43 both societies). The ranking of the variables is presented in Table . The highest ranked parameters indicative of axial involvement in a patient with PsA were presence of typical radiographic or MRI changes in the sacroiliac joints and/or spine followed by the presence of chronic back pain and then inflammatory back pain. A separate analysis of ASAS and GRAPPA members provided the similar results concerning the relevance of the variables. Conclusion: Objective signs of inflammatory involvement of the axial skeleton are the most important indicators of axial disease in PsA in the opinion of the experts. A prospective cohort study is currently being planned to address the value of these and other variables in defining axial involvement in PsA. Disclosure of Interests: Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Alice Gottlieb Grant/research support from: Boehringer Ingelheim, Incyte, Janssen, Novartis, UCB, Xbiotech, Consultant of: AbbVie, Allergan, Avotres Therapeutics, Beiersdorf, Boehringer Ingelheim, BMS, Celgene, Dermira, Incyte, Eli Lilly, Janssen, LEO Pharma, Novartis, Reddy Labs, Sun Pharmaceutical Industries, UCB, Valeant, Xbiotech, Laura C Coates: None declared, Vinod Chandran Grant/research support from: Abbvie, Celgene, Consultant of: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lily, Janssen, Novartis, Pfizer, UCB, Employee of: Spouse employed by Eli Lily, Philip Helliwell: None declared, Deepak Jadon: None declared, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant